Assessment of knowledge, awareness, practices and misconceptions among hypothyroid and hyperthyroid patients - Savitha, Kola; Kata, Srija; Chinthagani, Omkar; Gollapalli , Rajeev (International Journal of Research in Medical Sciences, 2023)
Background: In chronic illness there is a greater need for patient education to manage their symptoms, prevent complications, and have better therapeutic outcome and increase quality of life. Among chronic illnesses thyroid disorders are more common in the world. Our study aimed to assess knowledge, awareness, practices and misconceptions in thyroid patients in order to estimate the need of patient education and also counsel the patients for the same using counselling aids. Methods: A descriptive cross sectional study was conducted among 300 subjects in a secondary care hospital for a period of 6 months (February 2017- July 2017). The interviews were conducted in semi private areas in the hospital after taking informed consent by using a structured questionnaire which has been established for its validity and reliability. The results were calculated using descriptive statistical methods (frequency, percentage and mean). Results: Among the participants 23.33% were co-morbidities, majority of patients (83%) do not have family history. Only 32% of the participants have good knowledge, 52.66% have average knowledge and 15.33% patients have poor knowledge about symptoms. Though the knowledge on the dietary factors is considerable in participants, 31.95% of hypothyroid, 58.82% of hyperthyroid patients followed inappropriate dietary habits. 86.3% believed that patients with thyroid disorders need to take medications for their lifetime. Conclusions: The results conclude the need for patient education in thyroid disorders and also a need for clinical pharmacists in hospital setup to fill the gap between physician and patient to provide patient education and clarify misconceptions.